2015
DOI: 10.1016/j.landurbplan.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Integrated effects of urban morphology on birdsong loudness and visibility of green areas

Abstract: Abstract:The aim of this study is to determine how to increase birdsong loudness and the visibility of green areas in low-density residential areas by controlling urban morphological parameters. The spatial sound level distributions of birdsong at 12 sites sampled from a GIS database of Assen, the Netherlands, were simulated by noise mapping techniques and calculated using a MATLAB program on spatial sound level matrices. The visibilities of green areas are analysed and calculated by Visibility Analysis Graph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 68 publications
2
29
0
1
Order By: Relevance
“…In soundscape studies the full range of perceptible sounds in a given context at a given time is usually considered. Therefore, soundscape researchers are aiming to broaden the mapping process to other sources, both positive and negative (e.g., Hao, Kang, & Krijnders, 2015;. In order to represent existing soundscapes, two-dimensional maps could be developed as additional layers of landscape information.…”
Section: How Can We 'Represent' Soundscapes?mentioning
confidence: 99%
“…In soundscape studies the full range of perceptible sounds in a given context at a given time is usually considered. Therefore, soundscape researchers are aiming to broaden the mapping process to other sources, both positive and negative (e.g., Hao, Kang, & Krijnders, 2015;. In order to represent existing soundscapes, two-dimensional maps could be developed as additional layers of landscape information.…”
Section: How Can We 'Represent' Soundscapes?mentioning
confidence: 99%
“…In the case site, 4 typical music-related activities and 3 typical human sound-related activities were chosen at different locations at more than 100-m intervals, since previous studies indicated that there is no influence of sound-related activities on each other at this distance (Hao et al 2015). Music-related activities included Folk Dancing, Zombie Dancing, Qing Gong and Tai Ji.…”
Section: Sound-related Activitiesmentioning
confidence: 99%
“…Complementary actions involving masking of the traffic with natural sounds such as bird songs (Strohbach et al, 2009;2015b) are also useful.…”
Section: Implications In All Scalesmentioning
confidence: 99%